Electrospinning of Tetraphenylporphyrin Compounds into Wires. (29th November 2013) - Nuansing, Wiwat; Georgilis, Evangelos; de Oliveira, Thales V. A. G.; Charalambidis, Georgios; Eleta, Aitziber; Coutsolelos, Athanassios G.; Mitraki, Anna; Bittner, Alexander M.
<x xml:space="preserve">Abstract</x> Electrospinning is known mainly for polymers. We show that this simple technique allows to shape molecules that are useful for organic photovoltaic cells into wires, a morphology that is otherwise not generally obtained. A special advantage of our method is the simple mixing approach that allows to test blends of promising compounds, without the need for chemical pretreatment, modification or immobilization. Our materials are TPP‐NH2 (monoamino‐tetraphenylporphyrine) and FF‐TPP (diphenylalanine‐TPP), both candidates for electron donors in solar cells. We found that a mixture of FF‐TPP with FF (diphenylalanine) is especially advantageous for forming quasi infinitely long wires of 100 to 1000 nm diameter. We analyzed the wire morphology with optical, electron, and scanning force microscopy, and we used X‐ray diffraction and infrared spectroscopy to elucidate the internal structure. The wire is composed of intact molecules, but shows surprisingly low crystallinity, in stark contrast to the single components.